Cohort profiles of the cross-sectional and prospective participant groups in the second Diabetes MILES—Australia (MILES-2) study - Browne, Jessica L (BMJ Open, 2017)
PURPOSE: More research into the psychosocial aspects of diabetes is needed so that the health and quality of life of people with the condition can be improved. To fill this gap, we conducted the second Diabetes MILES—Australia study (MILES-2), a survey focused on psychological, behavioural and social aspects of diabetes. The aim of the MILES-2 study was to provide a (1) longitudinal follow-up of the original MILES 2011 study cohort; (2) cross-sectional assessment of a new cohort. PARTICIPANTS: Eligible participants were English-speaking Australians with type 1 or type 2 diabetes, aged 18–75 years. Longitudinal cohort participants were mailed/emailed study invitations directly by researchers. Random sampling (stratified by diabetes type, insulin use, state) of the National Diabetes Services Scheme (NDSS) database and nationwide advertisements were used to recruit new cohort participants. The final sample included N=2342 eligible respondents (longitudinal cohort: n=504; 2015 new cohort: n=1838); 54% had type 2 diabetes. FINDINGS TO DATE: Survey respondents were from an advantaged socioeconomic background compared to the general population. Respondents with type 1 diabetes were over-represented in the new cohort (45%) relative to the planned stratification (40% type 1 diabetes, 60% type 2 diabetes). Respondents with insulin-treated type 2 diabetes were under-represented in the new cohort relative to the stratified sampling (42% invited vs 50% response). Participants who completed both the 2011 and 2015 surveys were more likely than those completing the 2011 survey only to have type 1 diabetes, report a higher education and annual income, and live in metropolitan areas. Participant feedback indicated that the survey was perceived as relevant and valuable. FUTURE PLANS: The depth and breadth of the data available in this large sample will highlight unmet needs and priority areas for future investigation and, crucially, will inform policy, programme and intervention development and evaluation in Australia.